Recent Financial Crisis and the Role of Foreign Institutional Investors in India – With Reference to NSE - Saravanan, G.; Deo, Malabika (Indian Journal of Finance, 2011)
Indian stock market was opened to Foreign Institutional Investors on 14th September 1992. This opening up of capital markets to FIIs in emerging market countries has been perceived as beneficial by some researchers, while others are concerned about possible adverse consequences. Some researchers have perceived that the FIIs are responsible for spreading financial crisis and causing contagion in the international market. So, this study examines the role of FIIs in the Indian stock market during the recent financial crisis. The financial crisis began in July 2007, based on that, total sample period of nine years from January, 2000 to January, 2009 was divided into two sub samples as crisis and non-crisis period. For this analysis, regression model and graph has been used. Presence of FIIs in India during the crisis period shows the destabilizing impact on stock market in India, as their outflows from the market are for a shorter period that increased drastically during the crisis period. Further, during the non-crisis and crisis period, FIIs adopted positive feedback-trader strategy and negative feedback-trader strategy respectively and suggests that FIIs optimally use their portfolio and get huge returns both in crisis and non-crisis period.